Effect of Water Deficit Stress on Yield Performances in Wet Seeded Rice - Parveen, S; Humphreys, E; Ahmed, M (Bangladesh Rice Journal, 2018)
Worldwide fresh water scarcity and labour unavailability in agriculture are driving researchers and farmers to find management strategies that will increase water productivity and reduce labour requirement. Wet seeding instead of transplanting rice greatly reduces the labour requirement for crop establishment, while use of alternate wetting and drying (AWD) instead of continuous flooding reduces irrigation input. However, the safe threshold for irrigating wet seeded rice (WSR) at different crop stages has not been investigated. Therefore, experiment was conducted to determine the effects of different degrees of water stress during different crop growth stages on yield performance of WSR. This was done in greenhouse experiment in the 2011 wet season 2011 at the International Rice Research Institute, Los Baños, Philippines. In the experiment, water stresses were applied by withholding irrigation until soil water tension increased to 10, 20 or 40 kPa (kilo pascal) at 10 cm below the soil surface. Soil water tension was measured using 30 cm long guage tensiometer installed with the center of the ceramic cup. The stresses were applied during three crop stages: 3-leaf (3L) to panicle initiation (PI), PI to flowering (FL), and FL to physiological maturity (PM). The experiment also included a continuously flooded (CF) treatment. The number of drying events ranged from 8-12 during 3L-PI, 6-10 during PI-FL and 6-10 during FL-PM. There was a consistent trend for a decline in the number of irrigations and irrigation input with increasing irrigation threshold, and thresholds of 20 and 40 kPa resulted in significantly lower input than with CF. There were consistent trends for lower grain yield as the level of water deficit stress increased, and imposition of stresses of 20 and 40 kPa at any or all three stages significantly reduced grain yield compared with CF. There was a trend for the reduction in grain yield to be greater when the stresses were imposed at all three stages compared with a single stage, but the differences were not significant. There was a consistent trend for irrigation water productivity (WPi) to decrease as the irrigation threshold increased, with significantly lower values for a 40 kPa threshold at any stage, in comparison with CF. This was because the decline in water input to the pots was less than the decline in yield as the threshold increased. The results suggest that the optimum threshold for irrigation of WSR is 10 kPa during the vegetative and grain filling stages, and that the soil should be kept at close to saturation during PI-FL Bangladesh Rice j. 2017, 21(1): 1-12